Description Of Foreign Bodies in The Esophagus in The ORL-HNS Section Of RSUP M. Djamil Padang Period 2020-2021 (COVID-19 Pandemic) - Kevin Bryan Alghifari; Effy Huriyati; Hasmiwati Hasmiwati (The International Science of Health Journal, 2024)
Esophageal foreign bodies are sharp or blunt objects or food that get stuck and pinched in the esophagus due to swallowing, either intentionally or unintentionally. Symptoms of esophageal foreign body obstruction depend on the size, shape, type of foreign body and the location of the foreign body. The purpose of this study was to determine how the description of foreign bodies in the esophagus in the ORL-HNS section of Dr. M. Djamil Hospital during the period 2020-2021 (Covid-19 Pandemic). This study is a descriptive study using a cross-sectional design. The sample of this study was a population that met the inclusion criteria using the total sampling method. This data collection used patient medical records conducted at the center of the medical record facility at Dr. M. Djamil Padang Hospital. The subjects of this study were patients diagnosed with esophageal foreign body ingestion in the ORL-HNS department of Dr. M. Djamil Hospital Padang in the period 2020-2021 (COVID-19 Pandemic). In this study, 22 samples were obtained that met the inclusion and exclusion criteria of the study. The results of this study found that the percentage of sex ratio between men was comparable to women with the largest age group, namely 0-<10 years (59.09%). There were most main complaints felt by patients, namely swallowing pain (31.81%) with the duration of foreign body in the esophagus mostly >12-24 hours (50%). The location of the most foreign bodies was in the introitus of the esophagus (72.73%) with the most types of foreign bodies coins (50%) and the most management performed was esophagoscopy (100%) and no complications were found in 17 cases (77.27%) of 22 cases. During the covid-19 pandemic there was a decrease in the number of patients swallowed by foreign bodies compared to before the covid-19 pandemic, there were no differences in age, complaints, location, tye of foreign body, duration, management and complications.